Kinesin-2 Controls the Motility of RAB5 Endosomes and Their Association with the Spindle in Mitosis - Pupo, Emanuela (Int J Mol Sci, 2018)
RAB5 is a small GTPase that belongs to the wide family of Rab proteins and localizes on early endosomes. In its active GTP-bound form, RAB5 recruits downstream effectors that, in turn, are responsible for distinct aspects of early endosome function, including their movement along microtubules. We previously reported that, at the onset of mitosis, RAB5positive vesicles cluster around the spindle poles and, during metaphase, move along spindle microtubules. RNAi-mediated depletion of the three RAB5 isoforms delays nuclear envelope breakdown at prophase and severely affects chromosome alignment and segregation. Here we show that depletion of the Kinesin-2 motor complex impairs long-range movement of RAB5 endosomes in interphase cells and prevents localization of these vesicles at the spindle during metaphase. Similarly to the effect caused by RAB5 depletion, functional ablation of Kinesin-2 delays nuclear envelope breakdown resulting in prolonged prophase. Altogether these findings suggest that endosomal transport at the onset of mitosis is required to control timing of nuclear envelope breakdown.